How online hotel reviews affect consumer booking decisions / Amal Syafiqah Che Mohd Ruzima ... [et al.] - Che Mohd Ruzima, Amal Syafiqah; Sumarjan, Norzuwana; Sulong, Siti Nurhanifah; Azeman, Ainnin Sofea (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
Online evaluations function as a digital version of traditional word-of-mouth advertising, known as electronic word-of-mouth. As the digital economy grows and the digital revolution approaches, customers increasingly use social media to share their opinions online. Most consumers would not book a hotel without reading customer reviews, although some reviews do not accurately reflect the hotel's service and hospitality. Therefore, this study aims to investigate the connection between online reviews and booking intentions such as review volume, reviewer experience, and trust, which affect travellers’ booking decisions. Data was collected from 329 respondents through questionnaires. Convenience sampling was used and then analysed with regression analysis. The results indicate that all variables in online reviews, particularly trust in reviews, significantly influence booking intentions. However, price did not significantly moderate the relationship between review attributes and booking intentions. The study's findings can help hotel organisations improve by analysing their online presence and focusing on the content posted about them on social media.